The use of psychoactive substances and adolescents’ school performance - Pestana, Leonor (2017)
The use of psychoactive substances is a public health problem. The use of these substances usually starts during adolescence and is associated with school problems, namely poor school performance. Research Questions included which psychoactive substances interfere with school performance (learning environment, planning of studies, methods of studying, reading skills, study motivation, overall school performance) in adolescents. The purpose of the study was to analyse the relationship between the use of psychoactive substances and adolescents’ school performance. The Research Methods included a cross-sectional study. Data were collected through a questionnaire which included socio-demographic information, psychoactive substances and a school performance scale (adapted from Fermin, 2005). Non-probability sampling for convenience, with 380 students from 7th, 8th and 9th grade. Data were collected in 2011/2012 among students from a Basic School in the Portuguese Municipality of Viseu. Results: There was a 4.2% of prevalence of drug use: 4,3% in boys and 4.1% in girls. For both genders, the most commonly used drugs were hashish and marijuana (43.8%). Girls (p<0.001), younger students (p<0.001), those whose parents graduated from high-school or who have a higher education (p=0.019) and students who do not use drugs (p=0.000) do better in school. We concluded that drug abuse is associated with adolescents’ poorer school performance. It is therefore important to identify risk groups and develop policies to prevent youngsters from using psychoactive substances because of the major impact they have on individual, family and social levels.